PERANCANGAN PROGRAM SIMULASI PERINTAH DASAR JARINGAN KOMPUTER - Yuri Yudhaswana Joefrie (Foristek, 2013)
This research is intended to design software that is able to simulate the basic commands of the computer network. Simulation program is planned to serve for people who do not understand about computer networks and have a strong desirelearning the basics of computer networks. The design result of this research is command of ping, telnet, ftp, route, andifconfig. The design of the simulation program also produces 10 units or classes that contain the components of the specificactivity or program.